2006
DOI: 10.1002/pon.1123
|View full text |Cite
|
Sign up to set email alerts
|

Distress overlaps with anxiety and depression in patients with head and neck cancer

Abstract: Psychological problems in cancer patients often go unrecognized until they are specifically sought. This is more in patients with depression as they are reluctant to complain about their symptoms. The present study was carried out to evaluate the relation of distress with anxiety and depression in 123 patients with head and neck cancers using Distress Inventory for Cancer version 2 (DIC2) and the Hospital Anxiety and Depression scale (HADS). The mean DIC 2 scores were 24.6 while that of subscales ranged from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 25 publications
2
37
1
Order By: Relevance
“…As a result, they judge their QOL lower than the physician does. 37 In our study, the prevalence of anxiety (20.4%) and depression (26.5%) was significantly higher than in the general population (anxiety 5 5.9%, depression 5 15.8%) confirming the findings of other authors 38 and suggesting psychologic morbidity in patients with head and neck cancer even after curative treatment. Interestingly, patients treated by SNB showed significantly less fear of progression than patients who underwent SND (p 5 .024).…”
Section: Discussionsupporting
confidence: 93%
“…As a result, they judge their QOL lower than the physician does. 37 In our study, the prevalence of anxiety (20.4%) and depression (26.5%) was significantly higher than in the general population (anxiety 5 5.9%, depression 5 15.8%) confirming the findings of other authors 38 and suggesting psychologic morbidity in patients with head and neck cancer even after curative treatment. Interestingly, patients treated by SNB showed significantly less fear of progression than patients who underwent SND (p 5 .024).…”
Section: Discussionsupporting
confidence: 93%
“…The responses are recorded on a 5 point likert scale. The tool contains negatively and positively toned items to check for acquiescent responding 28,29,37 . QOL was measured with FACT-HN 30 , a total QOL score that also provides four primary QOL domains: physical well being, social well being, emotional well being and functional well being, and head and neck specific subscale.…”
Section: Methodsmentioning
confidence: 99%
“…The Distress Inventory for Cancer (DIC) since its first publication [32] has been substantially revised [33][34][35][36]. The data from a large sample of patients that had responded to the DIC version 2 were the basis, on which the present study is reported.…”
mentioning
confidence: 99%